Math anxiety and math teaching anxiety in primary school teachers in Costa Rica - Delgado-Monge, Islande Cristina (2024)
[Objective] This research project analyze math anxiety and anxiety experienced when teaching math by primary school teachers working for the Ministry of Public Education in Costa Rica. For this purpose, math anxiety and its three dimensions and math teaching anxiety and its four dimensions were determined. In addition, the influence of some variables such as academic performance, sex, and work experience on anxiety were also analyzed. [Methodology] The study was quantitative and had a sample of 372 practicing teachers (336 women and 36 men) from six regions of Costa Rica: San Carlos, North-North Zone, Limón, Los Santos, Puriscal, and Alajuela with ages between 23 and 63 years. Their experience as primary school teachers range from one year to 35 years, while 55 of them are still studying and 317 are not pursuing university studies. [Results] Higher academic performance is associated with lower MA and MTA scores. Furthermore, teachers suffer MA (Math Anxiety) and MTA (Math Teaching Anxiety), years of experience do not improve this situation, and less self-confident subjects experience more MTA. In addition, a positive correlation was found between MA, MTA, and their dimensions, being the correlations between GA (General Anxiety)-EA (Exam Anxiety), MA-GA, SC (Self-Confidence)-AMT (Attitude towards Math Teaching), and MTA-CK (Content Knowledge) the strongest. [Conclusions] The study concludes that the sample shows a significant percentage of MA and MTA, as well as their dimensions, which negatively affects attitude towards mathematics and teachers’ perception and self-confidence when teaching this subject.